2017
DOI: 10.3389/fmicb.2017.01207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Host Range, and Comparative Genomic Analysis of Temperate Ochrobactrum Phages

Abstract: Ochrobactrum and Brucella are closely related bacteria that populate different habitats and differ in their pathogenic properties. Only little is known about mobile genetic elements in these genera which might be important for survival and virulence. Previous studies on Brucella lysogeny indicated that active phages are rare in this genus. To gain insight into the presence and nature of prophages in Ochrobactrum, temperate phages were isolated from various species and characterized in detail. In silico analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 47 publications
(57 reference statements)
0
32
0
Order By: Relevance
“…POC9, in which the prophage regions were indicated manually) was applied. This enabled us to significantly extend the knowledge in this field since, in the previous works by Jackel et al [21,42,43] a total of 66 Ochrobactrum (pro)phages were indicated, while in our analysis, 277 prophages were identified within 104 out of the 113 analyzed genomes ( Supplementary Table S2). Moreover, by applying the vConTACT v2 tool [44], we compared vB_OspM_OC, vB_OspP_OH, and all identified Ochrobactrum prophages with the ProcaryoticViralRefSeq85-Merged database resources and the 12,817 bacteriophages present in the NCBI Genome database (as of 10 July 2019).…”
Section: Comparative Genomics Of Ochrobactrum Phagesmentioning
confidence: 59%
See 3 more Smart Citations
“…POC9, in which the prophage regions were indicated manually) was applied. This enabled us to significantly extend the knowledge in this field since, in the previous works by Jackel et al [21,42,43] a total of 66 Ochrobactrum (pro)phages were indicated, while in our analysis, 277 prophages were identified within 104 out of the 113 analyzed genomes ( Supplementary Table S2). Moreover, by applying the vConTACT v2 tool [44], we compared vB_OspM_OC, vB_OspP_OH, and all identified Ochrobactrum prophages with the ProcaryoticViralRefSeq85-Merged database resources and the 12,817 bacteriophages present in the NCBI Genome database (as of 10 July 2019).…”
Section: Comparative Genomics Of Ochrobactrum Phagesmentioning
confidence: 59%
“…The second phage, POI1126, originating from O. intermedium POI1126, exhibited similarities to the Sinorhizobium meliloti phage PCB5, the Erwinia pyrifoliae phage PEp14, and the Burkholderia cenocepacia phages DC1, Bcep22, and BcepIL02. Interestingly, the POI1126 phage genome was nearly identical to the unnamed plasmid of the O. intermedium strain LMG 3301, which suggests that this phage appears in a plasmid-like form in both strains [21].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous study demonstrated that the induction of Stx prophages was closely associated with the production of Stx and the transfer of stx genes among susceptible strains (Krüger et al, 2018). Although there is increasing interest in the prediction and functions of prophages found in different bacterial species, such as Ochrobactrum and Brucella (Hammerl et al, 2016;Jäckel et al, 2017), related information with respect to prophages in STEC genomes is lacking. In this study, the 40 complete whole-genome sequences of STEC strains generated by next-generation sequencing (NGS) technology and obtained from the NCBI database were used to understand the presence of different prophages within STEC genomes.…”
Section: Discussionmentioning
confidence: 99%